Cyber power and control: a perspective from strategic theory. Issue 2 (4th May 2019) - Zilincik, Samuel; Myklin, Michael; Kovanda, Petr
ABSTRACT: Cyber power has not been sufficiently examined from the perspective of strategic theory. This research aims to fill this gap by closely analysing the connection between cyber power and the concept of control. For this purpose, the authors use the method of theoretical analysis augmented by an examination of particular historical examples. The findings indicate that cyber sabotage and cyber subversion may be able to produce varying levels of control depending on the particular context of each situation. Cyber espionage alone is unable to produce any level of control, but it may enable other instruments to achieve a level of control.